A pooled analysis of the side effects of non-invasive Transcutaneous Auricular Vagus Nerve Stimulation (taVNS) - Giraudier, Manon; Ventura-Bort, Carlos; Szeska, Christoph; Weymar, Mathias (Frontiers in Human Neuroscience, 2025)
IntroductionTranscutaneous auricular vagus nerve stimulation (taVNS) is a promising technique for modulating vagal afferent fibers non-invasively and has shown therapeutic potential in neurological, cognitive, and affective disorders. While previous research highlights its efficacy, the safety profile of taVNS has been less extensively examined.MethodsThis study therefore aimed to systematically investigate side effects of taVNS in a large pooled dataset consisting of n = 488 participants, utilizing a standardized questionnaire to assess ten reported side effects. Analyses included effects of stimulation type (interval vs. continuous), stimulation duration, stimulation intensity and participant characteristics (age and gender) as potential modulators.ResultsThe findings support the safety of taVNS, with minimal and mild side effects reported across participants (M = 1.86, SD = 1.36). Although participants receiving sham stimulation were 32.4% less likely to report unpleasant feelings compared to participants receiving taVNS, this effect was driven primarily by low-end ratings (specifically, a rating of 1, indicating not at all when experiencing the corresponding side effect), thus suggesting limited clinical relevance. Interval stimulation notably reduced the likelihood of some side effects, particularly for neck pain, dizziness and unpleasant feelings, suggesting potential for optimizing taVNS protocols. Stimulation intensity and duration showed few statistically significant, but clinically minimal (i.e., very small) effects.ConclusionOverall, these findings demonstrate a favorable safety profile of taVNS, with mostly mild and transient effects, supporting its use as a suitable non-invasive tool in both research and clinical applications.